Utilisation and energy consumption of fair-access in sensor networks with selected grid topologies. (2017) - Peng, Miao; Xiao, Yang; Sun, Bo
In a typical wireless sensor network, besides gathering accurate data, obtaining a fair amount of data from each sensor node is also important. This paper is continuation effort of our previous work. In previous work, we derive tight upper bounds on network utilisation for linear and two rows grid topology. This paper extends the research to 3-4 rows grid topologies which are more complicate. The significance of these bounds is two-fold: first, they hold for any medium access control protocol under both single-channel and half-duplex radios; second, they are provably tight. Furthermore, we investigate energy consumption of medium access control for multi-hop sensor networks. Based on the tight upper bounds on network utilisation, we derive tight lower bounds on network energy consumption in a cycle for linear and 2-4 rows grid topology.